Mapeamento fisiológico e do crescimento da copa de coffea arabica cv. arara - Vilas Boas, Lissa Vasconcellos (2019)
In Brazil, the cultivation of coffee is of great importance, because coffee is the 5th most exported product of Brazilian agribusiness. And, its international importance comes from being cultivated in approximately 80 countries, making coffee one of the most traded agricultural products in the world. Among cultivars planted in Brazil, Arara cultivar has been highlighted by its high productive yield, high resistance to rust, high vigor, and good quality drink. This cultivar comes from the natural cross of the cultivar Obatã with the cultivar Catuai. Studies on the dynamics of the source and sink relations of the coffee tree in the field over the months are scarce and was the first time that the entire canopy of an adult coffee tree including vegetative and reproductive parts was mapped over the months with the aid of the geostatistics being applied to plant physiology. Thus, the present work had as objective to perform a mapping of the cup of Coffea arabica cv. Arara under field conditions and to describe the canopy dynamics throughout the months of the year through ecophysiological analyzes and vegetative and reproductive growth. For this, a vertical gradient (orthotropic axis) and a horizontal (plagiotropic axis) were established in the plant canopy. The orthotropic branch was separated in the upper, medium and lower portions, and the plagiotropics in proximal, intermediary and distal regions. They were still separated into branches from the north-south and east-west faces. Measurements were made from February 2017 to October 2018. The analyzes were photosynthetic active radiation (RFA), gas exchange, leaf area, number of leaves, leaf dry mass, dry mass of branches, number of fruits and rosettes, and dry mass of fruits. The dynamics of the Arara cultivar was dependent on the intensity of the RFA intercepted by the canopy leaves. The east-west faces of the coffee tree, which received higher RFA, had a higher photosynthetic rate, stomatal conductance and transpiration. The greater gas exchange of these portions increased the vegetative and reproductive capacity of the same. Thus, coffee leaves that received the highest RFA had greater leaf area, number of leaves, leaf dry mass, dry mass of branches, number of rosettes, number of fruits and dry mass of fruits. The dynamics of the coffee tree were altered after the harvest in 2017 with the defoliation and fall of plagiotropic branches, which allowed the inside portions of the plant to receive higher RFA and to be able to leverage the vegetative growth again and later the reproductive growth.